AKTIVITAS ANTIOKSIDAN DAN ANTIBAKTERI BAGIAN RANTING DAN BATANG TUMBUHAN KARAMUNTING (Melastoma malabathricum): Antioxidant and Antibacterial Activity of The Twigs and Stem Bark of Karamunting Plants (Melastoma malabathricum) - Nur Maulida Sari; Irawan Wijaya Kusuma; Rudianto Amirta; Nur Indriana Fitriah (Forestry Faculty of Universitas Hasanuddin, 2021)
East Kalimantan is one of the areas that have the potential for various traditional medicinal plants. Melastoma malabathricum (known locally as karamunting, senduduk) is an invasive plant in the family of Melastomataceae with a potential medicinal plant. This study explored the potential of twigs and stem bark of Karamunting (Melastoma malabathricum) for its antioxidant and antibacterial activity. The twigs and stem bark of Karamunting were macerated to yield ethanolic extract. The phytochemical screening was evaluated by Harborne and Kokate methods. Antioxidant activity was evaluated by DPPH radical scavenging assay. Antibacterial activity was examined using agar well diffusion method against Propionibacterium acnes. The results showed that the ethanol extracts of twigs and stem bark samples display an ability to inhibit DPPH free radical by 82% and 88% at 50 ppm concentration. Antibacterial activity of the twigs and stem bark samples showed potent activity to inhibit the P. acnes growth with 11.3 mm and 11 mm inhibition activity. Based on the results, the twigs and stem bark of M. malabathricum plants display potential as a natural antioxidant and antibacterial agent.